ANALISIS INDEKS KERUKUNAN ANTAR UMAT BERAGAMA DI KALANGAN SISWA SMA NEGERI DI KOTA SUMBAWA BESAR - JAZADI, FAIZ UNISA; WIDARI, IGA; JAZADI, IWAN (GANEC SWARA, 2020)
This research was conducted to analyze the index of harmony among religions among students at a state high school in the city of Sumbawa Besar. This research is quantitative type and the data are explained descriptively. The data obtained came from a questionnaire submitted to 50 students by the clustered random sampling method while still ensuring representation of each religion. The results obtained are among the state high school students who get a religious harmony index score of 76.22% and are included in the predicate very good. One of the optimization efforts that can be done is to strengthen religious relations between students.